Trait anger is related to the ability to recognize facial emotions—but only in men - Montag, Anna; Kersting, Anette; Suslow, Thomas (Frontiers in Psychology, 2025)
Trait anger is defined as a personality dimension of anger proneness. Previous research based on multimodal stimuli suggests that trait anger could be linked to poor emotion decoding. The present investigation examined the relationship between trait anger and emotion decoding ability for men and women. An emotion recognition task with images of emotional faces expressing anger, disgust, fear, sadness, surprise, or happiness was administered to 249 young adults (125 women). Participants completed the State–Trait Anger Expression Inventory (STAXI-2) along with other self-report instruments. Unbiased hit rate was calculated to assess emotion recognition accuracy. Women reported more trait anger than men. In men, but not in women, trait anger was related to negative affect variables. There were no sex differences in decoding facial emotions. For men, trait anger was negatively correlated with overall emotion recognition performance and specifically with the recognition of fear and disgust—even when controlling for relevant person variables. For women, trait anger was not related to facial emotion recognition. Compared to men with low trait anger, men with high trait anger appear to be worse at recognizing facial expressions of fear and disgust, which are negative emotions indicating being threatened or rejection.